First record of Sphenoptera (Chilostetha) egena Mannerheim, 1852 (Coleoptera: Buprestidae) from Kazakhstan with notes on its bionomics and distribution - Aizhan M. Tleppaeva (Acta Biologica Sibirica, 2025)
During the fieldwork conducted between 2021 and 2023 in the territory adjacent to the Tarbagatai Natural Park, a new species of jewel beetle (Coleoptera, Buprestidae), Sphenoptera (Chilostetha) egena Mannerheim, 1852, was discovered, marking a noteworthy addition to the fauna of Kazakhstan. Specimens of this species were collected in June from arid shrub-steppe slopes in the western part of the Tarbagatai Range, specifically near the village of Taskesken in the Karakol River floodplain. Prior to this discovery, Sphenoptera egena had only been reported from regions in Russia (Western and Eastern Siberia) and Mongolia. This paper presents a concise diagnostic overview of the genus Sphenoptera Dejean, 1833, along with a brief description of the species. Using ArcGIS PRO 3.1.1, we created a distribution map and modeled the favorable habitat conditions for Sphenoptera egena. Additionally, we provide a description of the background vegetation in the species' collection site. Photographs of the jewel beetle were captured using a Canon Kiss X4 camera with a Canon 60 mm Macro USM lens, illustrating the collection site of S. egena. Furthermore, other species, such as Agrilus sericans Kiesenwetter, 1857, and Meliboeus morawitzi (Semenov, 1905), were concurrently identified in the fauna of these steppe slopes. The identification of Sphenoptera egena not only enriches the inventory of jewel beetles in Kazakhstan, which currently includes over 200 species and subspecies across five subfamilies, twelve tribes, and twenty-eight genera, but also extends the known distribution range of this species.